Design Of A Digital Platform As An Effort To Empower Communities In The Tourism Sector Based On Local Wisdom - Davina V. A. Paendong; Diky Martin; Jessica Davalynda; M. Naufal Dwitama; Vanessa D. Celline; Rahmi Yulia Ningsih; Chairani Putri Pratiwi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Indonesia has vast tourism potential; however, the use of digital technology in managing and promoting destinations remains limited, particularly in small and rural areas. Limited access to technology, low digital literacy, and weak coordination among tourism stakeholders have become key challenges in enhancing the competitiveness of local tourism in the digital era. This study aims to design a digital platform as an effort to empower communities in the tourism sector based on local wisdom. The platform is designed to increase community participation, provide accessible information, and support community-based destination marketing and promotion. The research employs a Research and Development (R&D) method with a qualitative descriptive approach and adopts the Design Thinking development model, which consists of five stages: empathize, define, ideate, prototype, and test. Data were collected through questionnaires distributed to tourism business actors, travel agents, and tourists to explore their needs, perceptions, and challenges in utilizing digital technology. The study results in a design of a community-based digital tourism platform that integrates features of promotion, transactions, and coordination among local tourism stakeholders. The platform emphasizes the role of local communities as providers of tourism services such as homestays, local transportation, and tour guiding rooted in local wisdom. This concept is expected to foster local economic growth, strengthen cultural identity, and support the achievement of the Sustainable Development Goals (SDGs).